Impact of inhibition of complement by sCR1 on hepatic microcirculation after warm ischemia - Lehmann, Thorsten G.; Koeppel, Thomas; Münch, Steffen; Heger, Michael; Kirschfink, Michael; Klar, Ernst; Post, Stefan (Microvascular research, 2002)
Recent observations provide evidence that complement is implicated as an important factor in the pathophysiology of ischemia/reperfusion injury (IRI). Here, we assessed the effects of complement inhibition on hepatic microcirculation by in vivo microscopy (IVM) using a rat model of warm hepatic ischemia clamping the left pedicle for 70 min. Ten animals received the physiological complement regulator soluble complement receptor type 1 (sCR1) intravenously 1 min prior to reperfusion. Controls were given an equal amount of Ringer's solution (n = 10). Microvascular perfusion and leukocyte adhesion were studied 30 to 100 min after reperfusion by IVM. Microvascular perfusion in hepatic sinusoids was significantly improved in the sCR1 group (80.6 +/- 0.6% of all observed sinusoids were perfused [sCR1] vs 67.3 +/- 1.2% [controls]). The number of adherent leukocytes was reduced in sinusoids (49.9 +/- 3.4 [sCR1] vs 312.3 +/- 14.2 in controls [adherent leukocytes per square millimeter of liver surface]; P < 0.001) as well as in postsinusoidal venules after sCR1 treatment (230.9 +/- 21.7 [sCR1] vs 1906.5 +/- 93.5 [controls] [adherent leukocytes per square millimeter of endothelial surface]; P < 0.001). Reflecting reduced hepatocyte injury, liver transaminases were decreased significantly upon sCR1 treatment compared to controls. Our results provide further evidence that complement plays a decisive role in warm hepatic IRI. Therefore, we conclude that complement inhibition by sCR1 is effective as a therapeutical approach to reduce microcirculatory disorders after reperfusion following warm organ ischemia.
Gesehen am 17.02.2021